Sustainability in the translation classroom: Awareness through transformative practical activities - Elena Alcalde Peñalver; Alexandra Santamaría Urbieta (Ibérica)
Environmental sustainability is a topic that has gained increasing importance in recent years and is indeed part of the objectives set by the United Nations as part of the Agenda 2030. This has also become evident in the field of translation, as documents such as companies' sustainability reports have emerged, which need to be available to investors in different languages. There is a lack of information regarding previous investigations into the potential benefits of incorporating environmental sustainability themes into university-level translation studies. Whether such an approach can effectively raise student awareness and understanding of critical environmental issues remains unclear. Therefore, this study, grounded in English for Specific Purposes (ESP) principles, is based on a didactic experience in which a questionnaire is distributed among students enrolled in a Financial Translation course. The aim is to understand their perception of how a translation activity within the ESP context can promote specific knowledge about a subject and raise awareness about it. The results show that, indeed, translation can become a transformative practice for students to acquire specific knowledge and form their own opinion on current topics such as sustainability. This study contributes to the literature on ESP by highlighting the potential of translation as a tool for developing language proficiency, subject-specific knowledge, and critical thinking skills within a specialized domain.